2013
DOI: 10.1080/09064702.2014.922607
|View full text |Cite
|
Sign up to set email alerts
|

Effects of selenium and vitamin E supplementation on selenium distribution and meat quality of pigs

Abstract: The study was conducted on 60 pigs kept in individual pens. The animals were allocated to four groups. The growing-finishing pigs from the control group were fed with basic feed containing 0.3 mg selenium (Se) derived from Na 2 SeO 3 kg −1 and 60 mg of dl-α-tocopheryl acetate kg −1 . The remaining three groups were differentiated by adding 0.2 mg kg −1 Se-enriched yeast (Saccharomyces cerevisiae) and/or 60 mg vitamin E to feed (grower and finisher). Our results show that the addition of organic Se to inorganic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Authors who reported more efficient effect of dietary vitamin E supplementation on lipid oxidation (Faustmand and Want, 2000; Rey et al., 2004) used higher vitamin E dose (200 mg kg −1 ). However, others (Kawecka et al., 2013) who used low-supplementation dose (60 mg kg −1 ) did not find beneficial effect of vitamin E and organic Se on the quality of meat. In a previous study carried out by our group (Calvo et al., 2016), using a supplemented diet with inorganic Se and 100 mg kg −1 of vitamin E, a reduction in TBARS numbers was found when compared to a control group; however, muscle vitamin E accumulation was higher than that reported in the present study and differences between low-supplemented and high-vitamin E supplemented groups were of higher magnitude than those found in the present study for groups SeY and SeY-E.…”
Section: Resultsmentioning
confidence: 90%
“…Authors who reported more efficient effect of dietary vitamin E supplementation on lipid oxidation (Faustmand and Want, 2000; Rey et al., 2004) used higher vitamin E dose (200 mg kg −1 ). However, others (Kawecka et al., 2013) who used low-supplementation dose (60 mg kg −1 ) did not find beneficial effect of vitamin E and organic Se on the quality of meat. In a previous study carried out by our group (Calvo et al., 2016), using a supplemented diet with inorganic Se and 100 mg kg −1 of vitamin E, a reduction in TBARS numbers was found when compared to a control group; however, muscle vitamin E accumulation was higher than that reported in the present study and differences between low-supplemented and high-vitamin E supplemented groups were of higher magnitude than those found in the present study for groups SeY and SeY-E.…”
Section: Resultsmentioning
confidence: 90%
“…Moreover, other authors have reported no beneficial effect on meat quality when using a combination of dietary vitamin E (60 mg/kg) and Se at low doses (0.2 mg) (Kawecka, Jacyno, Matysiak, Kolodziej-Skalska & Pietruszka, 2013).…”
Section: Electrical Conductivity Ph Drip Loss and Meat Compositionmentioning
confidence: 92%
“…In addition, other meat quality characteristics such as water-holding capacity or color, which are considered useful parameters for evaluating quality and consumer acceptability, were affected by organic Se supplementation (Mahan et al 1999;Zhan et al 2007). However, the organic form (from Se-enriched yeast) used in the feed industry does not always show positive effects on meat quality characteristics (Juniper et al 2008(Juniper et al , 2011Kawecka et al 2013;Lisiak et al 2014). Organic forms such as Se-enriched yeast (SeY), are taken up via methionine transporter mechanisms and can be incorporated to selenoenzymes or in place of methionine into general body proteins (Suzuki and Ogra 2002) more readily than the inorganic form (Surai 2006).…”
Section: Introductionmentioning
confidence: 99%